Seasonal cycles in European agricultural commodity prices - Adusei Jumah; Robert M. Kunst (Institute for Advanced Studies (IHS), 2006)
This paper explores the seasonal cycles of European agricultural commodity prices. We focus on three food crops (barley, soft and durum wheat) and on beef. We investigate whether seasonality is deterministic or unit-root stochastic and whether seasonal cycle for specific agricultural commodities have converged over time. Finally, we develop time-series models that are capable of forecasting agricul-tural prices on a quarterly basis. Firstly, we find that seasonal cycles in agricultural commodity prices are mainly deterministic and that evidence on common cycles across countries varies over agricultural commodities. The prediction experiments, however, yield a ranking with respect to accuracy that does not always match the statistical in-sample evidence.
Keywords: C32; C53; Q11; 330; seasonal cycles; seasonal unit roots; forecasting; agricultural commodities; Preiswettbewerb; Landwirtschaft; Rohstoffpreis; Saisonschwankung; Europa